Separator for electrochemical devices and electrochemical device comprising the same
Patent Information
- Application Number
- CN202580021921.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-08-08
- Filing Date
- 2025-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
然而,最普遍使用的二氧化硅气凝胶存在问题,因为在二氧化硅合成期间产生的毒性是环境不期望的
[0024]通过包括设置在涂层上的平均孔径为50 nm至200 nm的纤维素纳米纤维气凝胶层,根据本公开的用于电化学装置的隔板可以具有优异的机械强度,同时具有低电阻,并且此外,具有通过使用纤维素纳米纤维而不是有毒二氧化硅而环境友好的优点。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure claims the benefit of the filing dates of Korean Patent Application No. 10-2024-0122182, filed with the Korean Intellectual Property Office on September 9, 2024, and Korean Patent Application No. 10-2025-0110017, filed with the Korean Intellectual Property Office on August 8, 2025, the entire contents of which are incorporated herein by reference.
[0002] This disclosure relates to a separator for an electrochemical device and an electrochemical device including the separator. Background Technology
[0003] Electrochemical devices are devices that convert chemical energy into electrical energy using electrochemical reactions. Recently, lithium-ion batteries have been widely used due to their high energy density, high voltage, long cycle life, and applicability in a variety of applications.
[0004] In components of such an electrochemical device, the separator may comprise a porous polymer substrate with a porous structure located between the positive and negative electrodes. The separator serves to isolate the positive and negative electrodes, preventing electrical short circuits between the two electrodes, and allowing electrolytes and ions to pass through it. Although the separator itself does not participate in the electrochemical reaction, its physical properties (such as wettability with the electrolyte, porosity, and thermal shrinkage) can affect the performance and safety of the electrochemical device.
[0005] Therefore, in order to enhance the physical properties of such separators, various methods have been explored, including adding coatings to porous polymer substrates and adding various materials to the coatings to improve their properties. For example, inorganic materials can be added to the coating to improve the mechanical strength of the separator, or inorganic materials or hydrates can be added to the coating to improve the flame retardancy and heat resistance of the polymer substrate.
[0006] In the coating, inorganic particles can be bonded to other inorganic particles via a polymer binder to form an interstitial volume, through which lithium ions can move. In other words, the coating, including the polymer binder and inorganic particles, serves to prevent thermal shrinkage of the separator while simultaneously facilitating the movement of lithium ions through the separator.
[0007] Meanwhile, when a thick coating is applied to a porous polymer substrate to overcome the thermal shrinkage problem of the separator, lithium ions may not be able to pass through the separator smoothly due to the relatively low porosity of the coating, thus potentially increasing the separator's resistance. To address this issue, a method has been attempted where a polymer substrate is coated with a thin layer of coating material, while simultaneously forming an aerogel layer with high porosity on top of the coating. Advantageously, the reduced coating thickness leads to a decrease in separator resistance. However, the most commonly used silica aerogel presents a problem because the toxicity generated during silica synthesis is environmentally undesirable.
[0008] Therefore, there is a need to develop novel separators for electrochemical devices that include an aerogel layer, which can reduce the resistance of the separator by being disposed on the coating, and is also non-toxic and therefore environmentally friendly. Summary of the Invention
[0009] Technical issues
[0010] The purpose of this disclosure is to provide a separator for an electrochemical device with low electrical resistance and excellent mechanical strength by including an aerogel layer with high porosity, wherein the aerogel layer comprises cellulose nanofiber (CNF) aerogel.
[0011] Technical solution
[0012] To achieve the above objectives, this disclosure provides a separator for an electrochemical device, comprising: a porous polymer substrate; a coating disposed on at least one surface of the porous polymer substrate and comprising inorganic particles; and an aerogel layer disposed on the coating and comprising cellulose nanofiber aerogel, wherein the aerogel layer has an average pore size of 50 nm or greater and 200 nm or less.
[0013] The aerogel layer may have a porosity of 80% or more and 99% or less.
[0014] Based on the total weight of 100 parts by weight of the aerogel layer, the content of the cellulose nanofiber aerogel may be 90 parts by weight or more and 99 parts by weight or less.
[0015] The aerogel layer may have a thickness of 0.5 μm or greater and 2 μm or less.
[0016] The coating may have a thickness of 0.3 μm or greater and 1.2 μm or less.
[0017] The coating may have a porosity of 40% or more and 70% or less by volume.
[0018] The cellulose nanofibers may have an average diameter of 5 nm or larger and 50 nm or smaller.
[0019] The cellulose nanofibers may have an aspect ratio of 1:50 or greater and 1:200 or smaller.
[0020] Based on the total weight of 100 parts by weight of the coating, the content of the inorganic particles may be 80 parts by weight or more and 95 parts by weight or less.
[0021] The inorganic particles may have an average diameter (D) of 200 nm or larger and 800 nm or smaller. 50 ).
[0022] This disclosure provides an electrochemical device including a positive electrode, a negative electrode, and a separator for the electrochemical device, wherein the separator for the electrochemical device is inserted between the positive electrode and the negative electrode.
[0023] Beneficial effects
[0024] By including a cellulose nanofiber aerogel layer with an average pore size of 50 nm to 200 nm disposed on the coating, the separator for electrochemical devices according to the present disclosure can have excellent mechanical strength while having low electrical resistance, and in addition, has the advantage of being environmentally friendly by using cellulose nanofibers instead of toxic silica. Detailed Implementation
[0025] Each construction of this disclosure will be described in more detail below, enabling those skilled in the art to readily perform this disclosure. However, this is merely illustrative, and the scope of this disclosure is not limited to the following.
[0026] As used herein, the term "comprising" is used to list materials, compositions, apparatus, and methods that may be used in this disclosure, but is not limited to the examples listed.
[0027] As used herein, the terms “about” and “substantially” are used in the sense of “being in or nearly in the presence of given manufacturing and material tolerances inherent in the circumstances” and are used to prevent unethical infringers from unfairly exploiting this disclosure, wherein exact or absolute figures are presented to aid in understanding this disclosure.
[0028] In this specification, when it is referred to as being set “on” a component, it means that the placement of other components between them is not excluded, but rather that other components may be further set between them, unless otherwise specifically stated.
[0029] As used herein, "electrochemical device" can refer to primary batteries, secondary batteries, supercapacitors, etc. More specifically, an electrochemical device can be a lithium-ion secondary battery, and can be pouch-shaped, cylindrical, prismatic, or coin-shaped, but its specific shape is not limited to these.
[0030] As used herein, the term "electrode" is intended to encompass both "positive" and "negative" electrodes, and may refer to those electrodes obtained by applying an electrode active material to at least one surface of a conductive material, followed by drying, without causing any chemical change in the electrochemical device. The types of conductive and electrode active materials are not limited, as long as they are suitable for use in the electrochemical device.
[0031] As used herein, "separator" generally refers to a functional separator in which a porous coating comprising inorganic materials and an adhesive is formed on at least one surface of a porous polymer substrate such as a polyolefin substrate or a nonwoven fabric. However, in this specification, it may refer to a separator in which a coating comprising inorganic materials is formed on at least one surface of a porous polymer substrate, and an aerogel layer comprising cellulose nanofiber aerogel is formed on the coating. Furthermore, the separator possesses porous characteristics by comprising multiple pores and functions as a porous ion-conducting barrier, allowing ions to pass through while blocking electrical contact between the negative and positive electrodes in an electrochemical device.
[0032] In this specification, "having pores" means that the material includes multiple pores, such that gaseous and / or liquid fluids can be transferred from one side of the material to the other through an interconnecting structure between the pores.
[0033] As used herein, a "porous polymer substrate" can refer to a porous membrane in which multiple pores are formed, electrically isolating the positive and negative electrodes to prevent short circuits between them. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can serve as an ion-conducting barrier, allowing lithium ions to pass through while blocking electrical contact between the positive and negative electrodes. At least some of the pores can form a three-dimensional network connecting the surface to the interior of the porous polymer substrate, and fluid can pass through the pores through the porous polymer substrate.
[0034] In this specification, "average diameter (D)" 50"Diameter" refers to the diameter at approximately 50% of the cumulative distribution of particle size based on diameter. The diameter can be measured using a laser diffraction method. For example, the particle size distribution is calculated by dispersing the powder to be measured in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500), and measuring the particle size dependence difference of the diffraction pattern as the particles pass through a laser beam. The particle size (D) can be measured by calculating the particle size at approximately 50% of the cumulative distribution of particle size based on diameter in the particle size analyzer. 50 ).
[0035] As used herein, "average pore size" refers to the average pore size in a material with multiple pores, such as a porous polymer substrate, coating, or aerogel layer. The average pore size can be calculated using scanning electron microscopy (SEM) images and image processing software (e.g., Sigma Scan Pro 5.0). Alternatively, the permeability curves for semi-dry and wet samples can be obtained using capillary flow porosimetry, and the size corresponding to the intersection of the two curves can be used as the average pore size.
[0036] As used herein, "aspect ratio" refers to the ratio of the diameter to the length of a fiber (such as a cellulose nanofiber) in a fibrous material where the fiber diameter and length can be measured. Specifically, the diameter, length, and aspect ratio of a fiber can be measured by scanning electron microscopy, and the aspect ratio refers to the average of the aspect ratios measured for any 20 fibers using scanning electron microscopy.
[0037] In this specification, the "average diameter" and "average length" of cellulose nanofibers can be calculated using conventional measurement methods known in the relevant art. For example, the average diameter of a cellulose nanofiber can be calculated by taking the longest straight-line distance between any two points on the cross-section connecting the fiber as the diameter, sampling approximately 10 fibers using a scanning electron microscope (SEM), and calculating the arithmetic mean of the diameters of these fibers. The average length of a cellulose nanofiber can be calculated as the arithmetic mean of the lengths of approximately 10 fibers used as a sample.
[0038] This disclosure will be described in more detail below.
[0039] This disclosure provides a separator for an electrochemical device.
[0040] According to one embodiment of this disclosure, a separator for an electrochemical device comprises: a porous polymer substrate; a coating disposed on at least one surface of the porous polymer substrate and comprising inorganic particles; and an aerogel layer disposed on the coating and comprising cellulose nanofiber aerogel, wherein the aerogel layer has an average pore size of 50 nm or greater and 200 nm or less. In the separator for the electrochemical device, the coating may be disposed on one or both surfaces of the porous polymer substrate. When the coating is disposed on both surfaces of the porous polymer substrate, the aerogel layer may be disposed on at least one of the coatings.
[0041] Compared to porous polymer substrates, coatings with relatively low porosity can prevent lithium ions from moving through the separator, thereby increasing the resistance of the separator in an electrochemical device containing the coating. Therefore, to reduce the separator resistance, the coating thickness needs to be reduced. However, when using only a coating with a small thickness, it is difficult to overcome the problem of thermal shrinkage of the separator. Therefore, the separator for an electrochemical device according to this disclosure has the advantages of low thermal shrinkage and low resistance by using a coating with a relatively thin thickness and simultaneously providing an aerogel layer with high porosity on the coating. Specifically, since cellulose nanofibers have excellent mechanical strength and heat resistance, the separator for an electrochemical device including an aerogel layer disposed on the coating can have excellent mechanical strength, such as puncture strength, and also a low thermal shrinkage rate. Furthermore, since the aerogel layer including cellulose nanofiber aerogel has high porosity, the separator for an electrochemical device according to this disclosure can also have a lower resistance than a conventional separator with only a coating disposed thereon. In addition, the cellulose nanofiber aerogel used for the separators of electrochemical devices is non-toxic and environmentally friendly because it is produced from cellulose nanofibers derived from polymers extracted from tree resources.
[0042] The average pore size of the aerogel layer can be 50 nm or larger and 200 nm or smaller. Specifically, the average pore size of the aerogel layer can be 50 nm or larger, 60 nm or larger, 70 nm or larger, 80 nm or larger, 90 nm or larger, or 100 nm or larger, and can also be 200 nm or smaller, 180 nm or smaller, 160 nm or smaller, 140 nm or smaller, 120 nm or smaller, or 100 nm or smaller. When the average pore size of the aerogel layer meets the above ranges, the pore size of the aerogel layer is large, so the electrolyte and lithium ions can easily move through the pores. Therefore, the resistance of the separator for an electrochemical device including an aerogel layer according to this disclosure can be low, and its electrolyte wettability can also be excellent. At the same time, if the average pore size of the aerogel layer is greater than the upper limit of the above ranges, the mechanical strength of the aerogel layer may be degraded due to the excessively large pore size, and therefore the mechanical strength (e.g., puncture strength) of the separator for an electrochemical device including an aerogel layer may also be degraded. Furthermore, if the average pore size of the aerogel layer is less than the lower limit of the above range, lithium ions may not be able to pass through the aerogel layer smoothly due to the small pore size, and the separator for electrochemical devices including the aerogel layer may have high resistance.
[0043] According to one embodiment of this disclosure, the aerogel layer may not include inorganic particles. Preferably, the aerogel layer may include cellulose nanofibers, a binder, and a dispersant. If inorganic particles are added to an aerogel slurry containing cellulose nanofibers, the dispersibility of the aerogel slurry may decrease due to the low compatibility of the inorganic particles. Therefore, the electrolyte ion channels in the formed aerogel layer can be abnormally altered by the inorganic particles, causing the microstructure of the aerogel layer to become non-uniform, and thus forming an unstable aerogel network. Therefore, even if the porosity and pore size of the aerogel layer are the same as those of the aerogel layer of this disclosure, the resistivity of the separator may be very high. Furthermore, due to the unstable aerogel network, the heat resistance of the separator may be poor, and the puncture strength of the separator may be poor. On the other hand, the aerogel layer of this disclosure, including cellulose nanofibers, a binder, and a dispersant, can have a stable aerogel network and therefore can have low resistivity and excellent heat resistance and puncture strength.
[0044] According to one embodiment of this disclosure, the porosity of the aerogel layer can be 80 vol% or more and 99 vol% or less. Specifically, the porosity of the aerogel layer can be 80 vol% or more, 82 vol% or more, 84 vol% or more, 86 vol% or more, 88 vol% or more, or 90 vol% or more, and can also be 99 vol% or less, 97 vol% or less, 95 vol% or less, 93 vol% or less, 91 vol% or less, or 89 vol% or less. When the porosity of the aerogel layer meets the above ranges, pores with an average pore size meeting the above ranges are sufficiently present in the aerogel layer, allowing lithium ions to move smoothly through the aerogel layer. Therefore, the separator for an electrochemical device including an aerogel layer can have low resistance.
[0045] According to one embodiment of this disclosure, the content of cellulose nanofiber aerogel based on the total weight of 100 parts by weight of the aerogel layer can be 90 parts by weight or more and 99 parts by weight or less. Specifically, the content of cellulose nanofiber aerogel based on the total weight of 100 parts by weight of the aerogel layer can be 90 parts by weight or more, 91 parts by weight or more, 92 parts by weight or more, 93 parts by weight or more, or 94 parts by weight or more, and the content of cellulose nanofiber aerogel based on the total weight of 100 parts by weight of the aerogel layer can also be 99 parts by weight or less, 98 parts by weight or less, 97 parts by weight or less, or 96 parts by weight or less. When the content of cellulose nanofiber aerogel in the aerogel layer meets the above ranges, the mechanical strength of the aerogel layer containing a sufficient amount of cellulose nanofiber aerogel with high mechanical strength can also be excellent. In addition, the heat resistance of the separator may also be excellent due to the aerogel layer. Therefore, the separator for electrochemical devices including the aerogel layer has the advantages of excellent mechanical strength (e.g., puncture strength) and heat resistance.
[0046] According to one embodiment of this disclosure, the aerogel layer may further include an adhesive, and the adhesive content may be 0.5 parts by weight or more and 8 parts by weight or less based on the total weight of 100 parts by weight of the aerogel layer. Preferably, the aerogel layer may be composed of cellulose nanofibers, an adhesive, and a dispersant. Specifically, the adhesive content may be 0.5 parts by weight or more, 1.5 parts by weight or more, 2.5 parts by weight or more, 3.5 parts by weight or more, or 4.5 parts by weight or more based on the total weight of the aerogel layer, and may also be 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less based on the total weight of the aerogel layer. When the adhesive content in the aerogel layer meets the above ranges, the adhesion between the aerogel layer and the coating on the porous polymer substrate and between the aerogel layer and the electrode can be improved, and therefore, the problem of aerogel layer separation during long-term operation of the electrochemical device can be minimized.
[0047] According to one embodiment of this disclosure, the adhesive may be at least one selected from the group consisting of: polyacrylic acid, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. The aerogel contains propionate, cyanoethyl pullullan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullullan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, and styrene-butadiene rubber. When the aerogel layer includes an adhesive, the adhesion between the aerogel layer and the electrode can be improved, and thus the problem of aerogel layer separation during long-term operation of the electrochemical device can be minimized.
[0048] According to one embodiment of this disclosure, the thickness of the aerogel layer can be 0.5 μm or greater and 2 μm or less. Specifically, the thickness of the aerogel layer can be 0.5 μm or greater, 0.75 μm or greater, 1 μm or greater, 1.25 μm or greater, or 1.5 μm or greater, and can also be 2 μm or less, 1.75 μm or less, 1.5 μm or less, 1.25 μm or less, or 1 μm or less. When the thickness of the aerogel layer meets the above ranges, lithium ions can easily pass through the aerogel layer with a small thickness, so the resistance of the separator may be low. In addition, since the total thickness of the separator for the electrochemical device can also be small, the electrochemical device including the separator for the electrochemical device can have a high energy density. At the same time, compared with the case where the thickness of the aerogel layer is too small, the separator for the electrochemical device including the aerogel layer disposed thereon can have excellent mechanical strength, and at the same time, its thermal shrinkage problem can be minimized.
[0049] According to one embodiment of this disclosure, the coating thickness can be 0.3 μm or greater and 1.2 μm or less. Specifically, the coating thickness can be 0.3 μm or greater, 0.5 μm or greater, or 0.7 μm or greater, and can also be 1.2 μm or less, 1 μm or less, 0.8 μm or less, or 0.6 μm or less. When the coating thickness meets the above ranges, the resistivity of the separator may be low due to the small thickness of the coating. Furthermore, an aerogel layer with high mechanical strength and porosity can be relatively adequately included within a limited separator size, so the separator for electrochemical devices including it can have excellent mechanical strength, such as puncture strength, and can have low resistivity.
[0050] According to one embodiment of this disclosure, the porosity of the coating can be 40% by volume or more and 70% by volume or less. Specifically, the porosity of the coating can be 40% by volume or more, 50% by volume or more, or 60% by volume or more, and can also be 70% by volume or less, 60% by volume or less, or 50% by volume or less. When the porosity of the coating meets the above ranges, pores can be sufficiently present in the coating, and therefore lithium ions can move smoothly through the pores, and therefore, the resistance of the separator used in the electrochemical device can be low. Furthermore, compared to the case where there are too many pores in the coating due to excessively high porosity, the separator for the electrochemical device according to this disclosure can have excellent mechanical strength, such as puncture strength.
[0051] According to one embodiment of this disclosure, the average pore size of the coating can be 40 nm or larger and 100 nm or smaller. Specifically, the average pore size of the coating can be 40 nm or larger, 50 nm or larger, or 60 nm or larger, and can also be 100 nm or smaller, 90 nm or smaller, 80 nm or smaller, 70 nm or smaller, or 60 nm or smaller. When the average pore size of the coating meets the above ranges, lithium ions can move smoothly through the pores of the coating, and therefore the resistance of the separator for the electrochemical device including it can be low. Furthermore, compared to the case where the average pore size of the coating is too large, the mechanical strength of the coating can be excellent, and therefore the puncture strength of the separator for the electrochemical device can also be excellent.
[0052] According to one embodiment of this disclosure, the average diameter of the cellulose nanofibers can be 5 nm or greater and 50 nm or less. Specifically, the average diameter of the cellulose nanofibers can be 5 nm or greater, 10 nm or greater, 15 nm or greater, 20 nm or greater, or 25 nm or greater, and can also be 50 nm or less, 45 nm or less, 40 nm or less, 35 nm or less, or 30 nm or less. When the average diameter of the cellulose nanofibers meets the above ranges, the adhesion of the aerogel layer can be improved due to the large surface area of the cellulose nanofibers. Therefore, the separator for an electrochemical device including the aerogel layer can have excellent adhesion to the electrode. Furthermore, since the volume of the cellulose nanofibers meeting the above average diameter ranges is not excessively large, the thickness of the aerogel layer including the cellulose nanofibers can also be small. Therefore, the thickness of the separator for an electrochemical device including the aerogel layer can also be thin, and therefore the energy density of the electrochemical device including the separator for an electrochemical device can also be high.
[0053] According to one embodiment of this disclosure, the average length of the cellulose nanofibers can be 1 μm or greater and 10 μm or less. Specifically, the average length of the cellulose nanofibers can be 1 μm or greater, 2 μm or greater, 3 μm or greater, 4 μm or greater, or 5 μm or greater, and can also be 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, or 4 μm or less. When the average length of the cellulose nanofibers meets the above ranges, the surface area of the cellulose nanofibers can be high, thus improving the adhesion of the aerogel layer. Therefore, the separator for an electrochemical device including an aerogel layer can have excellent adhesion to the electrode.
[0054] According to one embodiment of this disclosure, the aspect ratio of cellulose nanofibers can be 1:50 or greater and 1:200 or less. Specifically, the aspect ratio of cellulose nanofibers can be 1:50 or greater, 1:60 or greater, 1:70 or greater, 1:80 or greater, 1:90 or greater, or 1:100 or greater, and can also be 1:200 or less, 1:180 or less, 1:160 or less, 1:140 or less, 1:120 or less, or 1:100 or less. When the aspect ratio of cellulose nanofibers meets the above ranges, the adhesion of cellulose nanofibers can be excellent, and the mechanical strength can also be excellent. When the aspect ratio of cellulose nanofibers meets the above ranges, cellulose nanofibers can have excellent adhesion and excellent mechanical strength. If the aspect ratio of cellulose nanofibers is too low, the adhesion of the aerogel layer is poor; conversely, if the aspect ratio is too high, the breaking strength of the fibers may be poor, and therefore the mechanical strength of the aerogel layer may be weakened. Furthermore, when the aspect ratio of cellulose nanofibers meets the above-mentioned range, the problem of excessive aggregation of cellulose nanofibers can be prevented. In addition, the problem of reduced air permeability due to blockage of the pores of the aerogel layer can be prevented.
[0055] According to one embodiment of this disclosure, based on the total weight of 100 parts by weight of the coating, the content of inorganic particles can be 80 parts by weight or more and 95 parts by weight or less. Specifically, based on the total weight of 100 parts by weight of the coating, the content of inorganic particles can be 80 parts by weight or more, 85 parts by weight or more, or 90 parts by weight or more, and based on the total weight of 100 parts by weight of the coating, the content of inorganic particles can also be 95 parts by weight or less, 90 parts by weight or less, or 85 parts by weight or less. When the content of inorganic particles in the coating meets the above ranges, the coating sufficiently contains inorganic particles, thereby effectively reducing the thermal shrinkage problem of the porous polymer substrate.
[0056] According to one embodiment of this disclosure, the inorganic particles may have an average diameter (D) of 200 nm or greater and 800 nm or less. 50Specifically, the inorganic particles can have an average diameter of 200 nm or larger, 300 nm or larger, or 400 nm or larger, and can also have an average diameter of 800 nm or smaller, 700 nm or smaller, 600 nm or smaller, or 500 nm or smaller. When the average diameter of the inorganic particles meets the above ranges, sufficient gaps can exist between the inorganic particles filling the coating, thus the porosity and permeability of the coating can be excellent. Therefore, lithium ions can move smoothly through the coating, and thus the resistance of the separator for the electrochemical device including the coating can be low. Furthermore, when the average diameter of the inorganic particles meets the above ranges, the dispersibility of the inorganic particles in the coating slurry used to form the coating can be excellent, and the thickness of the coating formed by the slurry can also be small.
[0057] According to one embodiment of this disclosure, the inorganic particles may not undergo oxidation and / or reduction reactions within the operating voltage range of the electrochemical device (e.g., 0V to 5V relative to Li / Li⁺). Specifically, the inorganic particles may be at least one selected from the group consisting of: BaTiO₃, Pb(Zr,Ti)O₃(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1, 0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc-tin hydroxide (ZnSn(OH)6), zinc-tin oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), and antimony pentoxide (Sb2O5).
[0058] According to one embodiment of this disclosure, the coating may further include an adhesive. The adhesive may be at least one selected from the group consisting of: polyacrylic acid, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, and styrene-butadiene rubber.
[0059] According to one embodiment of this disclosure, the porous polymer substrate can be a porous membrane in which multiple pores are formed, electrically isolating the positive and negative electrodes to prevent short circuits between them. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can be an ion conduction barrier that allows lithium ions to pass through while blocking electrical contact between the positive and negative electrodes. At least some of the pores can form a three-dimensional network connecting the surface to the interior of the porous polymer substrate, and fluid can pass through the pores through the porous polymer substrate.
[0060] Porous polymer substrates can include materials that are physically and chemically stable to electrolytes as organic solvents. For example, porous polymer substrates can include, but are not limited to, resins selected from: polyolefins (such as polyethylene, polypropylene, and polybutene), polyvinyl chloride, polyethylene terephthalate, polycyclic olefins, polyethersulfone, polyamides, polyimides, polyamide-imides, nylon, polytetrafluoroethylene, and copolymers or mixtures thereof. Preferably, polyolefin resins can be used. Polyolefin resins can be processed to relatively small thicknesses and allow coating slurries to be easily applied thereto, and are therefore suitable for manufacturing electrochemical devices with high energy densities.
[0061] The porous polymer substrate can have a single-layer or multi-layer structure. It may include two or more polyolefin resin layers with different melting temperatures (Tm) to provide a shut-off function in the event of thermal runaway of the battery. For example, the porous polymer substrate may include a polypropylene layer with a relatively high melting temperature and a polyethylene layer with a relatively low melting temperature. Preferably, the porous polymer substrate may have a three-layer structure, wherein polypropylene, polyethylene, and polypropylene are stacked in this order. The polyethylene layer can melt as the battery temperature rises to a predetermined temperature or higher, thereby closing the pores and preventing thermal runaway of the battery.
[0062] According to one embodiment of this disclosure, the thickness of the porous polymer substrate can be 4 μm or greater and 15 μm or less. Specifically, the thickness of the porous polymer substrate can be 4 μm or greater, 6 μm or greater, 8 μm or greater, or 10 μm or greater, and can also be 15 μm or less, 13 μm or less, 11 μm or less, 9 μm or less, or 7 μm or less. By controlling the thickness of the porous polymer substrate within the above ranges, the volume of the electrochemical device can be minimized, while the positive and negative electrodes are electrically insulated, thereby increasing the amount of active material contained in the electrochemical device.
[0063] According to one embodiment of this disclosure, a porous polymer substrate may include pores with an average diameter of 0.01 μm or greater and 1 μm or less. Specifically, the size of the pores included in the porous polymer substrate may be 0.01 μm or greater, 0.02 μm or greater, 0.03 μm or greater, or 0.04 μm or greater, and may also be 1 μm or less, 0.09 μm or less, 0.08 μm or less, 0.07 μm or less, or 0.06 μm or less. Preferably, the pore size may be 0.02 μm or greater and 0.06 μm or less. By controlling the pore size of the porous polymer substrate within the above ranges, the air permeability and ionic conductivity of the manufactured separator can be controlled.
[0064] The porous polymer substrate can have an air permeability of 10 s / 100cc or greater and 100 s / 100cc or less. Specifically, the air permeability of the porous polymer substrate can be 10 s / 100cc or greater, 20 s / 100cc or greater, 30 s / 100cc or greater, 40 s / 100cc or greater, or 50 s / 100cc or greater, and can also be 100 s / 100cc or less, 90 s / 100cc or less, 80 s / 100cc or less, or 70 s / 100cc or less. Preferably, the air permeability of the porous polymer substrate can be 50 s / 100cc or greater and 70 s / 100cc or less. When the air permeability of the porous polymer substrate is within the above range, the air permeability of the manufactured separator can be provided within a range suitable for ensuring the output characteristics and cycle characteristics of the electrochemical device.
[0065] Air permeability (s / 100cc) refers to the time (in seconds) it takes for 100 cc of air to pass through a predetermined area of a porous polymer substrate or separator under constant pressure. Air permeability can be measured using a Gurley densometer according to ASTM D726-58, ASTM D726-94, or JIS-P8117. For example, 100 cc of air at an air pressure of 0.304 kPa or 1.215 kN / m³ can be measured using a Gurley 4110 N device. 2 Under water pressure, passing through 1 square inch (or 6.54 cm) 2 The time taken to pass through a sample. For example, the Asahi Seiko EG01-55-1MR apparatus can be used to measure the time it takes for 100 cc of air to pass through a 1 square inch sample at room temperature under a constant pressure of 4.8 inches of water.
[0066] The porous polymer substrate can have a porosity of 10 vol% or higher and 70 vol% or lower. Specifically, the porosity of the porous polymer substrate can be 10 vol% or higher, 20 vol% or higher, 30 vol% or higher, or 40 vol% or higher, and can also be 70 vol% or lower, 60 vol% or lower, or 50 vol% or lower. Preferably, the porosity of the porous polymer substrate can be 40 vol% or higher and 60 vol% or lower. When the porosity of the porous polymer substrate is within the above range, the ionic conductivity of the manufactured separator can be within a range suitable for ensuring the output characteristics and cycle characteristics of the electrochemical device.
[0067] Porosity refers to the volume percentage of pores relative to the total volume of each of the aerogel layer, coating, and porous polymer substrate. Porosity can be measured by methods known in the art. For example, it can be measured using the BET (Brunauer-Emmett-Teller) method with nitrogen adsorption, capillary flow porometer, or water or mercury intrusion porometer.
[0068] This disclosure provides an electrochemical device.
[0069] Electrochemical devices may include the separators described above for electrochemical devices.
[0070] According to one embodiment of this disclosure, an electrochemical device includes a positive electrode, a negative electrode, and a separator for the electrochemical device, wherein the separator for the electrochemical device is insertable between the positive and negative electrodes. In the electrochemical device according to one embodiment of this disclosure, any description overlapping with the description of the separator for the electrochemical device will be omitted.
[0071] Electrochemical devices convert chemical energy into electrical energy through electrochemical reactions, and include primary batteries and secondary batteries. Secondary batteries are capable of being charged and discharged, and include rechargeable batteries, nickel-cadmium batteries, nickel-metal hydride batteries, etc. Lithium secondary batteries use lithium ions as ionic conductors, and examples include, but are not limited to, non-aqueous electrolyte secondary batteries including liquid electrolytes, all-solid-state batteries including solid electrolytes, lithium polymer batteries including gel polymer electrolytes, and lithium metal batteries using lithium metal as the negative electrode.
[0072] Since the electrochemical device includes the separator described above according to the present disclosure, it has the advantage of low resistance and excellent output characteristics because lithium ions can move smoothly through the separator due to the high porosity of the aerogel layer. Furthermore, since the separator including the aerogel layer has excellent mechanical strength (e.g., puncture strength) and heat resistance, the electrochemical device including the separator also has the advantage of excellent stability.
[0073] According to one embodiment of this disclosure, the positive electrode may include: a positive electrode current collector; and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material, a conductive material, and an adhesive resin. The positive electrode active material may include one, or a mixture of two or more, selected from: layered compounds, such as lithium manganese oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), etc., or compounds substituted with one or more transition metals; compounds of the formula Li1+x Mn 2-x Lithium manganese oxides represented by O4 (wherein x is 0 to 0.33), such as LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxides (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; represented by the formula LiNi 1-x M x O2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); Ni-site type lithium nickel oxides represented by the formula LiMn 1-x M x O2 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1), or Li2Mn3MO8 (wherein M=Fe, Co, Ni, Cu or Zn); LiMn2O4 in which a part of Li in the formula is substituted with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0074] According to one embodiment of the present disclosure, the negative electrode may include: a negative electrode current collector; and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material, a conductive material and a binder resin. The negative electrode may include one or a mixture of two or more selected from the following as the negative electrode active material: lithium metal oxides; carbon materials such as non-graphitizable carbon and graphite-based carbon; metal composite oxides such as Li x Fe2O3 (0≤x≤1), Li x WO2 (0≤x≤1), Sn x Me 1-x Me' y O z (Me=Mn, Fe, Pb or Ge; Me'=Al, B, P, Si, an element of Groups 1, 2 or 3 of the periodic table, or a halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni based materials; and titanium oxides.
[0075] According to one embodiment of this disclosure, the conductive material may be, for example, any one or a mixture of two or more conductive materials selected from the group consisting of: graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon, and polyphenylene derivatives. More specifically, the conductive material may be one or a mixture of two or more conductive materials selected from the group consisting of: natural graphite, artificial graphite, super-p, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.
[0076] According to one embodiment of this disclosure, the current collector is not particularly limited, as long as it has high conductivity without causing chemical changes in the battery, and examples include stainless steel, copper, aluminum, nickel, titanium, calcined carbon, and aluminum or stainless steel that has been surface-treated with carbon, nickel, titanium, silver, etc.
[0077] According to one embodiment of this disclosure, polymers commonly used in electrodes in the art can be used as adhesive resins. Non-limiting examples of such adhesive resins include, but are not limited to, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetatebutyrate, and cellulose acetate propionate. Propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose.
[0078] According to one embodiment of this disclosure, the positive electrode slurry used to form the positive electrode active material layer may contain a dispersant, wherein the dispersant may be a pyrrolidone-based compound. Specifically, the dispersant may be N-methyl pyrrolidone (ADC-01, LG Chemical Co., Ltd.).
[0079] According to one embodiment of this disclosure, the electrochemical device may further include an electrolyte, and the electrolyte may be having A + B - Salts with a structure in which A + It may contain alkali metal cations (e.g., Li) + Na+ K + ions composed of ) or combinations thereof. Furthermore, B - This can include, for example, PF6 - BF4 - Cl - ,Br - I - ClO4 - AsF6 - CH3CO2 - CF3SO3 - N(CF3SO2)2 - C(CF2SO2)3 - Anions of or combinations thereof, and the salts may be soluble or dissociated in organic solvents selected from: propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide (DMSO), acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or mixtures thereof, but not limited thereto.
[0080] One embodiment of this disclosure provides a battery module comprising a battery containing an electrochemical device as a unit cell, a battery pack comprising the battery module, and a device comprising the battery pack as a power source. Specific examples of the device include, but are not limited to, power tools powered by an electric motor; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), or plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles including e-bikes or e-scooters; electric golf carts; and power storage systems.
[0081] The present disclosure will be described in detail below with reference to embodiments. However, embodiments according to the present disclosure can be modified in various different forms, and the scope of the present disclosure should not be construed as limited to the embodiments described below. The embodiments provided in this specification are intended to explain the present disclosure more completely to those skilled in the art.
[0082] Examples and Comparative Examples
[0083] Manufacturing of separators for electrochemical devices
[0084] <Example 1>
[0085] Polyethylene resin was extruded and a porous polymer substrate (thickness: 11 μm) was manufactured from it using a wet process.
[0086] Preparation of alumina powder (particle size (D)) 50 The inorganic particles were prepared as follows: polyacrylic acid (K-702, Lubrizol Corp.) as a binder and sodium carboxymethyl cellulose (CMC-Na) (SG-L02, GL Chem Co., Ltd.) as a dispersant. The prepared inorganic particles, binder, and dispersant were added to water at a weight ratio of 87.5:0.3:12.2, and then the inorganic particles were pulverized and dispersed to prepare the coating slurry.
[0087] The coating slurry was applied to one surface of a porous polymer substrate using a doctor blade via a bar coating method, and then dried with air at 50°C using a hot air gun to form a coating on one surface of the porous polymer substrate. At this point, the porosity of the coating was 40% by volume, and the coating thickness was 1 μm.
[0088] A cellulose nanofiber hydrogel composed of cellulose nanofibers (average diameter: 30 nm, average length: 3 μm, aspect ratio: 1:100) was prepared. An aerogel slurry containing 95 parts by weight of cellulose nanofiber hydrogel, 3 parts by weight of binder, and 2 parts by weight of dispersant was rapidly cooled with liquid nitrogen and then freeze-dried to prepare a solid aerogel. The solid aerogel was coated onto one surface of a coating layer to form an aerogel layer (cellulose nanofiber aerogel content: 95 wt%). At this point, the porosity of the aerogel layer was 85% by volume, its average pore size was 100 nm, and its thickness was 1 μm.
[0089] <Example 2>
[0090] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that: a 10 μm thick polyethylene porous polymer substrate was used, a coating with a thickness of 1 μm was formed on both surfaces of the porous polymer substrate using a coating slurry, and an aerogel layer with a thickness of 1 μm was formed on one surface of one of the coatings.
[0091] <Example 3>
[0092] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that: a 10 μm thick polyethylene porous polymer substrate was used, a coating with a thickness of 0.5 μm was formed on each of the two surfaces of the porous polymer substrate using a coating slurry, and an aerogel layer with a thickness of 1.5 μm was formed on one surface of one of the coatings.
[0093] <Example 4>
[0094] The separator for the electrochemical device was manufactured in the same manner as in Example 3, except that an aerogel layer with a thickness of 1.5 μm was formed on both surfaces of the coating.
[0095] <Example 5>
[0096] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that an aerogel layer with a volume porosity of 83% and an average pore size of 80 nm and a thickness of 1 μm was formed on one surface of the coating.
[0097] <Comparative Example 1>
[0098] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that a coating with a thickness of 1.5 μm was formed on one surface of the porous polymer substrate using a coating slurry, and one surface of the coating was not coated with an aerogel layer.
[0099] <Comparative Example 2>
[0100] The separator for the electrochemical device was manufactured in the same manner as in Example 2, except that a coating slurry was used to form a coating with a porosity of 40% by volume and a thickness of 1.5 μm on both surfaces of the porous polymer substrate, and no aerogel layer was formed.
[0101] <Comparative Example 3>
[0102] The separator for the electrochemical device was manufactured in the same manner as in Example 2, except that both surfaces of the porous polymer substrate were coated with an aerogel layer instead of a coating, and no coating was formed. In this case, the thickness of each aerogel layer was 1.5 μm.
[0103] <Comparative Example 4>
[0104] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that an aerogel layer with an average pore size of 35 nm and a porosity of 85% by volume was formed on one surface of the coating.
[0105] <Comparative Example 5>
[0106] The separator for the electrochemical device was manufactured in the same manner as in Example 1, except that an aerogel layer with an average pore size of 600 nm and a porosity of 85% by volume was formed on one surface of the coating.
[0107] <Reference Example 1>
[0108] In Reference Example 1, to form the aerogel layer, 75 parts by weight of cellulose nanofiber hydrogel, 15 parts by weight of inorganic particles for forming the coating, 9 parts by weight of binder, and 1 part by weight of dispersant were mixed together to prepare an aerogel slurry. This slurry was rapidly cooled with liquid nitrogen and then freeze-dried to prepare a solid aerogel. A separator for an electrochemical device was manufactured in the same manner as in Example 1, except that one surface of the coating was coated with the solid aerogel to form an aerogel layer (cellulose nanofiber aerogel content: 75% by weight).
[0109] <Measuring the resistance of the partition>
[0110] Each separator of the examples and comparative examples was sandwiched between SUS plates to manufacture a coin cell. An electrolyte comprising 1 M LiPF6 and a mixture of ethylene carbonate and methyl ethyl carbonate in a 1:2 volume ratio was injected into the coin cell. To measure the resistance of the coin cell, electrochemical impedance spectroscopy was performed using a VMP3 (BioLogic Science Instruments) at 25°C under conditions of 10 mV amplitude and a scan range of 0.1 Hz to 1 MHz. The results are shown in Tables 1 to 3 below.
[0111] <Evaluation of the wet shrinkage rate of the partition>
[0112] The separators of the examples and comparative examples were prepared into samples each with a size of 5 cm × 5 cm, and each sample was inserted into an aluminum bag with a size of 7 cm × 10 cm. 1 g of the following electrolyte solution was injected into the bag, and the bag was sealed.
[0113] As the electrolyte solution, a 1M solution of lithium salt LiPF6 was used, comprising 2% by weight vinylene carbonate (VC) as an additive and a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) mixed in a 3:7 weight ratio. After storing the sealed bag in a convection oven at 135°C for 30 minutes, the partition was removed, and the thermal shrinkage rates in the MD and TD directions were calculated according to [(initial length of the sample - length after 0.5 hours of storage at 135°C) / (initial length of the sample)] × 100 (%). The results are shown in Tables 1 to 3 below.
[0114] <Measurement of the puncture strength of the septum>
[0115] The maximum load value was measured when a needle with a diameter of 1 mm (0.5 mmR) was punctured at a speed of 120 mm / min into the separators manufactured in each of the Examples and Comparative Examples for use in electrochemical devices, and the results are shown in Table 1 below. Five measurements were performed on each separator using an Instron testing machine according to ASTM D5748-95 and ASTM D4649, and the average value was calculated using the testing machine. The results are shown in Tables 1 through 3 below.
[0116] [Table 1]
[0117]
[0118] [Table 2]
[0119]
[0120] [Table 3]
[0121]
[0122] As shown in Tables 1 and 2 above, it can be confirmed that the separators for electrochemical devices of Examples 1 to 5 (where the aerogel layer is formed on a coating containing inorganic materials) have a resistance twice as low as that of the comparative examples, and also exhibit excellent mechanical strength, such as puncture strength. Furthermore, it can be confirmed that the separators of the examples comprising cellulose nanofiber aerogels with excellent heat resistance have a wet heat shrinkage rate twice as low as that of the comparative examples. Simultaneously, it can also be confirmed that the separator for electrochemical devices of Example 4 (where both the coating and the aerogel layer are formed on two surfaces) has a significantly lower resistance, despite the separator thickness being greater than that of the comparative examples.
[0123] Furthermore, it can be confirmed that in the cases of the separators for the electrochemical device in Comparative Examples 4 and 5, where the average pore size of the aerogel layer is outside the range of 50 nm to 200 nm, the resistance, puncture strength, and thermal shrinkage rate of the separator are inferior to those of the embodiments, even though the porosity of the aerogel layer is different from that of the present disclosure. Specifically, it is shown that in the case of Comparative Example 5 (where the average pore size of the aerogel layer exceeds 200 nm), the puncture strength is poor even though the thickness of the separator for the electrochemical device is greater than that of Example 1. In addition, it is shown that in the case of Comparative Example 4 (where the average pore size of the aerogel layer is less than 50 nm), the resistance is significantly higher even though the thickness of the separator for the electrochemical device is less than that of Example 1.
[0124] Meanwhile, it can be confirmed that in the case of Reference Example 1, where the aerogel layer further comprises inorganic particles, the microstructure within the aerogel layer becomes non-uniform due to the inorganic particles, preventing the electrolyte from smoothly passing through the aerogel layer, and therefore, the resistance of the separator is not as good as that of the embodiment. Furthermore, it can be confirmed that in the case of the Reference Example, the aerogel network within the aerogel layer is unstable, and therefore the heat resistance and puncture strength of the separator are inferior to those of the embodiment.
[0125] In summary, through experimental examples, it can be confirmed that, since the separator of this disclosure includes a coating and an aerogel layer comprising cellulose nanofiber aerogel on a porous polymer substrate, and the average pore size of the aerogel layer satisfies 50 nm to 200 nm, the separator has low electrical resistance and thermal shrinkage rate, and at the same time, its mechanical strength is also excellent.
Claims
1. A separator for an electrochemical device, comprising: Porous polymer substrate; A coating, wherein the coating is disposed on at least any one surface of the porous polymer substrate and comprises inorganic particles; and An aerogel layer, wherein the aerogel layer is disposed on the coating and comprises cellulose nanofiber aerogel, The aerogel layer has an average pore size of 50 nm or larger and 200 nm or smaller.
2. The separator for an electrochemical device according to claim 1, wherein the aerogel layer has a porosity of 80% or more and 99% or less by volume.
3. The separator for an electrochemical device according to claim 1, wherein, Based on the total weight of 100 parts by weight of the aerogel layer, the content of the cellulose nanofiber aerogel is 90 parts by weight or more and 99 parts by weight or less.
4. The separator for an electrochemical device according to claim 1, wherein the aerogel layer has a thickness of 0.5 μm or greater and 2 μm or less.
5. The separator for an electrochemical device according to claim 1, wherein the coating has a thickness of 0.3 μm or greater and 1.2 μm or less.
6. The separator for an electrochemical device according to claim 1, wherein the coating has a porosity of 40% or more and 70% or less by volume.
7. The separator for an electrochemical device according to claim 1, wherein the cellulose nanofibers have an average diameter of 5 nm or greater and 50 nm or less.
8. The separator for an electrochemical device according to claim 1, wherein the cellulose nanofibers have an aspect ratio of 1:50 or greater and 1:200 or less.
9. The separator for an electrochemical device according to claim 1, wherein the content of the inorganic particles is 80 parts by weight or more and 95 parts by weight or less, based on 100 parts by weight of the total weight of the coating.
10. The separator for an electrochemical device according to claim 1, wherein the inorganic particles have an average diameter (D) of 200 nm or greater and 800 nm or less. 50 ).
11. An electrochemical device, comprising: positive electrode; negative electrode; And a separator for an electrochemical device according to any one of claims 1 to 10, The separator for the electrochemical device is inserted between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Metal containing photoresist developer composition, and method of forming patterns incouding step of developing using the composition
KR1020240122182A
Functional food compositions using Discorea bulbifera and production method thereof
KR1020250110017A
